(untitled) (Brazilian Journal of Oceanography, 2020)
Mangroves and coral reefs are among the major ecosystems of tropical and subtropical coastlines. The Andaman group of islands, situated at the juncture of Bay of Bengal and Indian Ocean, are one of the richest coastal ecosystems of India in terms of biodiversity. Since the tsunami waves of 2004 affected this region severely, the outer fringes as well as inland areas of these islands faced extensive ecological degradation. Mayabunder is one such place of this region, where corals and mangroves had experienced both natural and anthropogenic threat. Considering the notable vulnerability of this coastal environment, the present study aimed to assess the transformations of the coral and mangrove ecosystems at Mayabunder both in pre-tsunami and post-tsunami periods till the present year using multi-temporal satellite imageries and geospatial techniques. Results showed that the areal coverage of healthy living coral reefs was reduced by 466.56 ha (10.42 %) from 1990 to 2000. Afterwards, the coupled ecosystem had experienced serious degradation again during the 2000−2010 phase. The areal coverage of dense mangroves decreased by 47.37%, whereas the area of dead coral covers showed a significant rise of 55.52%. However, partial restoration of both mangroves as well as healthy corals had also been observed here in recent years. It was raised from the extensive field visits and feedbacks from local inhabitants that this restoration initiative could become more effective if a participatory mode of management is adopted.